ZETDC inspect to connect mobile application - Makuni, Tsitsidzashe (Midlands State University, 2020)
The need to develop an Inspect to Connect Mobile Application (ZETDC ITC) was necessitated by the lack of a facility that was convenient in the operations of electrical inspection to the connection procedures. Clients had to incur expenses of travelling from one point to another for them to get inspection and connection services, despite having to travel long distances to ZETDC offices they also had to wait for hours in queues waiting to be attended to. Employees also ended up having burnout syndrome and fatigue due to working extra hours as well as writing some monotonous weekly and monthly reports. The development of the new system using android and PHP (for back end application) helped to curb the challenges faced by customers as well as the employees since most of the client electrical inspection and connection procedures are now done at the comfort of their homes and employees reports are now auto generated by the system. Data was gathered using interviews, observations and questionnaire as the data gathering methodologies with the intention of understanding the operations of the old system and identify problems that were being faced as well as determining the requirements and functionality that was being expected in the new system. Feasibility study was undertaken and the results permitted the project team to go to the next development procedure. Alternatives were evaluated on which way to develop the new system and in-house development was recommended since it was the best alternative among others. The system was installed using parallel changeover as the changeover strategy since this was considered safe enough to countermeasure the risks of data loss in case of a system failure. The project team decided to implement all the maintenance strategies since they considered them to serve different purposes. The new system should accommodate the use of USSD code for nonandroid users, as well as for the clients with internet access problems, for client fault reporting and purchase of ZETDC electricity tokens